Comparative Evaluation and Optimization of Auxin Type and Concentration on Rooting Efficiency of Photinia × fraseri Dress: Stem Cuttings Using Response Surface Methodology - Gülcay Ercan Oğuztürk; Müberra Pulatkan; Cem Alparslan; Türker Oğuztürk (Plants)
This study aimed to evaluate and optimize the effects of three auxin types—indole-3-butyric acid (IBA), naphthaleneacetic acid (NAA), and indole-3-acetic acid (IAA)—applied at four concentrations (1000, 3000, 5000, and 8000 ppm) on the rooting performance of Photinia × fraseri Dress. stem cuttings. The experiment was conducted under controlled greenhouse conditions using a sterile perlite medium. Rooting trays were placed on bottom-heated propagation benches maintained at a set temperature of 25 ± 2 °C to stimulate root formation. However, the actual rooting medium temperature—measured manually every four days from the perlite zone using a calibrated thermometer—ranged between 18 °C and 22 °C, with an overall average of approximately 20 ± 2 °C. The average values of these root-zone temperatures were used in the statistical analyses. Rooting percentage, root number, root length, callus formation, and mortality rate were recorded after 120 days. In addition to classical one-way ANOVA, response surface methodology (RSM) was employed to model and optimize the interactions between auxin type, concentration, and temperature. The results revealed that 5000 ppm IBA significantly enhanced rooting performance, yielding the highest rooting percentage (85%), average root number (5.80), and root length (6.30 cm). RSM-based regression models demonstrated strong predictive power, with the model for rooting percentage explaining up to 92.79% of the total variance. Temperature and auxin concentration were identified as the most influential linear factors, while second-order and interaction terms—particularly T·ppm—contributed substantially to root length variation. These findings validate IBA as the most effective exogenous auxin for the vegetative propagation of Photinia × fraseri Dress. and provide practical recommendations for optimizing hormone treatments. Moreover, the study offers a robust statistical modeling framework that can be applied to similar propagation systems in woody ornamental plants.